Addition of Molasses Ameliorates Water and Bio-Floc Quality in Shrimp Pond Water - Yustian Rovi Alfiansah; Jens Harder; Matthew James Slater; Astrid Gärdes (Tropical Life Sciences Research, 2022)
Suspended particulate matter, phytoplankton and bacteria can be exploited to form larger aggregates, so-called bio-flocs. These serve as feeds for cultured shrimps, govern inorganic nutrients and load bacteria including pathogens. The current study aimed to simulate aggregate formation from available particulate matter in shrimp pond water and investigate quality of aggregates as well as possible impact to the pond water. Molasses was added to cylindrical tanks containing shrimp pond waters, and the tanks were rolled for 48 h. Besides water quality (inorganic nutrients and physical parameters), the researchers investigated and separated bacterial community compositions (BCC) to free-living (FL) and bio-flocs/particle-attached (PA) bacteria via 16S rRNA amplicon sequencing, and measured macro-molecules contents (carbohydrates, lipids and proteins) in the bio-flocs. Molasses addition increased bacterial numbers in the bio-flocs to two-fold higher than the FL’s. Moreover, potential probiotics such as Halomonas, Psychrobacter, Mesonia and Chromohalobacter were detected associated to bio-flocs and dominated the BCC. In contrast, bio-flocs without molasses showed 4-fold less carbohydrates and harboured elevated potential pathogens such as Vibrio and Alteromonas. Results show that molasses (at C/N ratio 1:2) increases pH (to 8.2 ± 0.09 and 8.0 ± 0.04 after 24 h and 48 h, respectively) in pond water, improving beneficial biofloc formation. Molasses also increased carbohydrates and proteins in bio-flocs and maintained abundances of beneficial bacteria resulting in low inorganic nutrient concentrations. Thus, molasses is suitable for shrimp farming to improve rearing processes.